2020
DOI: 10.1007/s42235-020-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Modifier-free Approach to Fabricate Antistatic Superhydrophobic Composite Coatings with Remarkable Thermal Stability and Corrosion Resistance

Abstract: Research on antistatic superhydrophobic surfaces has attracted widespread attention in some fields. However, in the application of superhydrophobic materials, fabricating stable and practical superhydrophobic surfaces through facile and low-cost approaches still faces considerable challenges. Herein, a polyphenylene sulfide (PPS)-based antistatic superhydrophobic composite coating with a high water contact angle (166°) and a low sliding angle (2°) was fabricated on a Q345 steel surface through a simple spray-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The corresponding element distribution on the CSC coating surface is displayed in Figure 3d, and it can be seen that elements of various additives are distributed on the coating surface. According to our previous work [33], the EDS spectrum of the obtained CSC coating surface is shown in Figure 3e and it can be easily seen that the CSC coating is composed of C, O, F, Si, Ce, and S. Additionally, the peaks of the F, Si, Ce, and S were attributed to the presence of PTFE, PDMS, CeO 2 , and PPS in the MSC coating, respectively. Figure 3b exhibits the corresponding schematic diagram of superhydrophobicity.…”
Section: Surface Morphology and Wettabilitymentioning
confidence: 54%
See 2 more Smart Citations
“…The corresponding element distribution on the CSC coating surface is displayed in Figure 3d, and it can be seen that elements of various additives are distributed on the coating surface. According to our previous work [33], the EDS spectrum of the obtained CSC coating surface is shown in Figure 3e and it can be easily seen that the CSC coating is composed of C, O, F, Si, Ce, and S. Additionally, the peaks of the F, Si, Ce, and S were attributed to the presence of PTFE, PDMS, CeO 2 , and PPS in the MSC coating, respectively. Figure 3b exhibits the corresponding schematic diagram of superhydrophobicity.…”
Section: Surface Morphology and Wettabilitymentioning
confidence: 54%
“…Tetrapropylammonium bromide (TPAB) was obtained from the Sinopharm Chemical Reagent Co. Ltd (Shanghai, China). According to our previous work [33], 3D flower-like CeO 2 particulates were synthesized with a simple procedure. PPS (average Mn: 1 × 10 4 , yellow color powder) was purchased from Sigma-Aldrich Co. Ltd (Saint Louis, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by bionics, fabricating super-hydrophobic surface on materials has been regarded as an admirable technology of excellent anti-corrosion performance [9,10] . Previous literatures have demonstrated that the real contact area between super-hydrophobic interface and corrosive medium is extremely small on account of plenty of air pockets trapping underneath the laser-induced micro-nano structures [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few studies on flexible conductive superhydrophobic surfaces have been reported [26][27][28]. As is known, superhydrophobic surfaces depend on two main factors: surface roughness and low surface energy [29,30]. The surface roughness is mainly provided by various surface treatment methods, and low surface energy can be obtained from fluorinated or long chain polymers [31].…”
Section: Introductionmentioning
confidence: 99%